PENGARUH SELF-AWARENESS TERHADAP TINGKAT KECEMASAN PADA MAHASISWA - Wildan Ahimsa Effendi; Fadli Firmansyah; Asri Syiar Mentari (Elsia: Jurnal Psikologi Manusia, 2025)
Anxiety is a psychological condition where a person feels worried, afraid, tired, nervous which is caused by several factors, including personality type, genetics, and events that trigger the stress. Self-awareness is the ability to accept and understand several things that make a person an individual, including personality, behavior, values, beliefs, emotions and thoughts. This research wants to prove the influence that occurs between self-awareness and anxie specifically for students in university. This research uses quantitati regression research. Using academic anxiety scale by Praba Raras (2021) and for the Self-Awareness variable, using a scale from Oparekhe Hilapok (2017). Data collection was carried out by distributing questionnaires online and obtained as many as 150 respondents as samples. From the research it is found that Self-Awareness has a negative influence where the anxiety found students was lower when their self-awareness was higher. This findi is in line with previous research such as Akhnaf (2022) and research by Babanejad et al., (2015).